Modelling The Deformation Behaviour of Recycled Aluminium Alloys Reinforced with Alumina Oxide Undergoing Finite Strain Deformation - Khoo, Chui Siang; Mohd Nor, Mohd Khir; Maat, Norzarina; Abdul Samad, Mohd Syazwan (Research Progress in Mechanical and Manufacturing Engineering, 2023)
Recycled aluminium alloys have shown major economic and environmental benefits. Even though numerous works have been implemented to improve the properties, including the inclusion of alumina oxide (Al2O3) as aluminium matrix composites (AMCs), there are very limited efforts to predict the deformation behaviour of such material numerically. This is important before appropriate applications can be further established. Therefore, this research project is conducted to predict the deformation behaviour of aluminium alloy AA6061 reinforced alumina oxide through numerical analysis and compare the results with experimental test data published by another researcher. The deformation behaviour of the recycled aluminium alloy reinforced alumina oxide is tested over a range of strain rate (6x10-1s-1, 6x10-2s-1 and 6x10-3s-1) via uniaxial tensile test. Referring to the experimental data, the flow stress model – MAT_098: Simplified Johnson-Cook model in LS-DYNA is chosen. The constants of the material model are defined by the characterisation of experimental data. Next, LS-DYNA software is used to perform finite element analysis of the uniaxial tensile test. The numerical results are validated against experimental data. There is a good match between the numerical results and the experimental results.